HUBUNGAN ANTARA EMPLOYEE WELL-BEING DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN PT. GEPREK MANTUL WILAYAH MAGELANG - Siti Nurma Ria Ulfa; Dewi Handayani Harahap (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
The food and beverage industry has a fast-paced work rhythm that risks depressing employee psychological well-being, as identified at PT Geprek Mantul in the Magelang region, where extra-role behavior has not yet developed optimally. This quantitative study aims to analyze the relationship between employee well-being and organizational citizenship behavior (OCB). Involving 110 respondents selected through purposive sampling, data were collected using a Likert scale and processed through a Pearson correlation test. The research findings indicate that the majority of employees have high levels of well-being (55.5%) and OCB (76.4%). The results of the hypothesis test indicate a strong and significant positive relationship between the two variables with a correlation value of r = 0.631 and p = 0.001. The R Square value of 0.398 indicates that employee well-being contributes 39.8% to the variation in OCB behavior. Analysis per dimension reveals that psychological well-being has the most dominant influence (r = 0.624) compared to the life and workplace dimensions. The main conclusion of this study confirms that improving employee well-being holistically is a crucial strategy to encourage the emergence of voluntary initiatives that support organizational effectiveness. Companies are advised to prioritize the stability of psychological conditions and a comfortable work environment to strengthen the prosocial culture and team productivity within PT Geprek Mantul in order to achieve sustainable long-term organizational success through an internal human resource maintenance scheme.